2020
DOI: 10.1111/jcmm.15740
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed lnc‐NOS2P3‐miR‐939‐5p axis in chronic heart failure inhibits myocardial and endothelial cells apoptosis via iNOS/TNFα pathway

Abstract: As more and more patients survive their initial cardiovascular diseases, chronic heart failure (CHF) becomes the leading cause of elderly hospitalization and death worldwide. 1 Therapeutic strategies improvements didn't increase CHF survival rate effectively. 2 CHF is a progressive disease, and the critical pathogenesis is myocardial pathological remodelling, initially triggered by multiple signal and network interactions 3 including overactivation of many neurohormones and inflammation factors after myocardia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The media were provided by HyClone, Thermo Scientific (UT, USA). HUVECs (ATCC®CRL-1730™) were cultivated in 10% FBS-RPMI 1640 medium (GIBCO, NY, USA) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The media were provided by HyClone, Thermo Scientific (UT, USA). HUVECs (ATCC®CRL-1730™) were cultivated in 10% FBS-RPMI 1640 medium (GIBCO, NY, USA) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Excessive apoptosis of endothelial cells severely interferes with endothelial integrity and endothelial function, resulting in endothelial damage, which is closely associated with the occurrence and the development of various cardiovascular diseases [2][3][4][5][6]. NO, which is predominantly synthesized by eNOS in endothelial cells, is a vasoactive substance secreted by endothelial cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell apoptosis triggers vascular endothelial injury [1] and is the pathophysiological basis of numerous cardiovascular diseases, including atherosclerosis, hypertension, aneurysm, and pulmonary hypertension [2][3][4][5][6]. In endothelial cells, nitric oxide (NO) predominantly synthesized by endothelial nitric oxide synthase (eNOS) has an anti-apoptotic effect, and therefore, it is a crucial vascular protective gasotransmitter [7].…”
mentioning
confidence: 99%
“…A previous study showed that restricting the TNF-α can inhibit the process of CHF, which may become a novel way to treat CHF (77). The excitation-contraction coupling of cardiomyocytes is closely related to calcium ion (Ca 2+ ) regulation.…”
Section: Discussionmentioning
confidence: 99%